2011
DOI: 10.1155/2011/284961
|View full text |Cite
|
Sign up to set email alerts
|

Real and Pseudoaccommodation in Accommodative Lenses

Abstract: In the attempt to manage presbyopia, different intraocular lens designs have been proposed such as monofocal IOLs with monovision or multifocal IOLs. Even though the lenses mentioned offer satisfactory visual results, contemporary ophthalmology has not completely answered the presbyopic dilemma by simulating the accommodative properties of the crystalline lens itself. Accommodative IOLs were designed to fill this gap and provide satisfactory vision for all distances by restoring some degree of “pseudoaccommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In particular, reading speed evaluation based upon reading acuity, the critical print size, and the mean and maximum reading speeds has provided interesting insights into the near-visual performance of presbyopic patients prior to and following therapy. Clinical studies have investigated the reading performance of patients with various models of multifocal and accommodating IOLs [2–5, 911, 16, 17, 22], corneal inlays [7], or following laser refractive surgery [1921]. Also, the reading performance of cataract patients has been analyzed in detail [17, 67, 23], and reading tests have been shown to be useful for estimating potential acuity [14, 68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, reading speed evaluation based upon reading acuity, the critical print size, and the mean and maximum reading speeds has provided interesting insights into the near-visual performance of presbyopic patients prior to and following therapy. Clinical studies have investigated the reading performance of patients with various models of multifocal and accommodating IOLs [2–5, 911, 16, 17, 22], corneal inlays [7], or following laser refractive surgery [1921]. Also, the reading performance of cataract patients has been analyzed in detail [17, 67, 23], and reading tests have been shown to be useful for estimating potential acuity [14, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a number of studies have been performed with these standardized logarithmic reading charts and have shown that it is possible to obtain detailed information about the reading performance achieved with bi-, multi-focal, and accommodative IOLs [2–5, 911, 16, 17, 22], corneal inlays, [7], monofocal IOLs [18, 23], and following LASIK/LASEK [15] or refractive laser treatment for presbyopia [1820]. Interesting insights into the reading performance of cataract patients have also been obtained with the Bailey-Lovie Word Reading Charts [14] and with the MNREAD Charts as e.g.…”
Section: Main Textmentioning
confidence: 99%
“…We also measured pseudoaccommodation which is a phenomenon attributed to gaining near vision without changes in refractive power of the ocular system. 6 …”
Section: Methodsmentioning
confidence: 99%
“…5 The changes in anterior–posterior position of the IOL resulting from contraction of ciliary muscle or vitreous pressure and its multiple focal points with alterations in lens curvature and refractive power are mainly the source of accommodative capacity of this implant. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Different optical solutions incorporated to IOLs have been proposed to correct for this lack of accommodation. Accommodative IOLs are intended to change the eye power [10,11], although their actual implementation has not been successful yet [12][13][14]. Other IOLs incorporated multifocality, distributing the light in the image plane across separated foci [15,16].…”
Section: Introductionmentioning
confidence: 99%